Perhitungan Harga Pokok Produksi Pembuatan Canopy Pada CV Latahzan Di Kota Ambon - Malawat, Zainal Abidin; Musaid, Sri Astuti Musaid (Journal of Applied Accounting, 2024)
CV Latahzan is one of automatic vehicle store that producing all goods made of iron. The objective of this research is to know how much the main production cost of canopy product at CV Latahzan on September 2023. The data analysis technique that used by the researcher is the calculation of main production cost of canopy product using full costing method. The result of this research shows that the main production cost of 2 x 5 size canopies is IDR 15.942.000Keywords ; Cost Of Goods Sold, Full Costing Method